2022
DOI: 10.1038/s41598-022-17567-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil-to-lymphocyte ratio for the fatality of COVID-19 patients complicated with cardiovascular diseases and/or risk factors

Abstract: Previous studies have reported that a high neutrophil-to-lymphocyte ratio (NLR) is associated with disease severity and poor prognosis in COVID-19 patients. We aimed to investigate the clinical implications of NLR in patients with COVID-19 complicated with cardiovascular diseases and/or its risk factors (CVDRF). In total, 601 patients with known NLR values were selected from the CLAVIS-COVID registry for analysis. Patients were categorized into quartiles (Q1, Q2, Q3, and Q4) according to baseline NLR values, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…These findings also suggest an imbalance between the innate immune response (neutrophils) and the adaptive immune response (lymphocytes), indicating increased inflammation and a weakened immune response. [17] Moreover, Higaki et al [18] demonstrated that elevated NLRs at follow-up are associated with increased mortality, emphasizing the dynamic nature of NLR as a response to treatment. Unlike our findings, this study revealed baseline NLR as an inadequate predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also suggest an imbalance between the innate immune response (neutrophils) and the adaptive immune response (lymphocytes), indicating increased inflammation and a weakened immune response. [17] Moreover, Higaki et al [18] demonstrated that elevated NLRs at follow-up are associated with increased mortality, emphasizing the dynamic nature of NLR as a response to treatment. Unlike our findings, this study revealed baseline NLR as an inadequate predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated a suitable value for NLR as a predictive marker for COVID-19 patients complicated with cardiovascular disorders. Results of their study showed that follow-up NLR had better overall predictive value, compared to baseline NLR, indicating the importance of time of sample collection for the prediction of mortality in complicated COVID-19 patients [26]. Also, in this regard, a multi-infammatory index along with CRP and NLR has been studied recently [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SARS‐CoV‐2‐infected T cells may also cause cytopathic effects on T cells. Therefore, the ratio of neutrophils to lymphocytes increases 18,24 . Even though the etiopathogenesis of PTE in COVID‐19 is not completely understood, factors related to the acute inflammatory response to the disease may be contributing to a dysregulation of the equilibrium of procoagulant and anticoagulant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ratio of neutrophils to lymphocytes increases. 18 , 24 Even though the etiopathogenesis of PTE in COVID‐19 is not completely understood, factors related to the acute inflammatory response to the disease may be contributing to a dysregulation of the equilibrium of procoagulant and anticoagulant mechanisms. Accordingly, it could reasonably be predicted that higher NLR values were also found in COVID‐19 patients with PTE when compared to patients with non‐PTE.…”
Section: Discussionmentioning
confidence: 99%